Nutritional assessment of athletes - Driskell, Judy A. (Judy Anne); Wolinsky, Ira (CRC Press, 2011)
"Evaluating dietary intake, determining energy metabolism, and conducting other nutritional assessments are essential in understanding the relationships between diet, exercise, health, and physical performance, especially in athletes. Several methods exist, each with their own advantages and limitations. Extensively referenced and filled with numerous tables and figures, this timely book focuses on the nutritional assessment of both recreational and professional athletes, including children, adolescents, and adults. In one volume, it presents methods for all types of nutritional evaluations, including dietary, anthropometric, physical activity needs, biochemical, and clinical assessments"--Provided by publisher